ANALISIS PERBANDINGAN MODEL KEBANGKRUTAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE DI BEI - Putri Aprilia, Shofi; Damayanti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Bankruptcy is a situation where a company cannot fulfill its obligations because it does not have adequate funds. The aim of this research is to use the Altman, Springate, and Zmijewski models to examine the estimated bankruptcy of real estate and property companies listed on IDX between 2020-2023. Using a sample, namely purposive sampling with a sample size of 22 companies and using the type of data, namely secondary information in the form of financial reports. Research findings show that the predictions made by each model vary. Based on the 2020-2023 average, the Altman model predicts that there will be 5 samples in the healthy category, while the Springate model predicts that there will be 16 samples in the healthy category, then the Zmijewski model predicts that there will be no companies in a bankruptcy situation.